LOCAL GOVERNMENT AUTHORITY IN EXERCISING RIGHTS OF CULTURAL PROTECTION AND PRESERVATION IN MALINAU REGENCY - Yahya Ahmad Zein; Fathurrahman Fathurrahman; Adymas Putro Utomo; Bernardo Idalina Leto; Himawan Estu Bagijo (Universitas Lampung, 2025)
This study critically examines the authority of local government in protecting and preserving regional culture in Malinau Regency. It aims to analyze the legal basis for cultural preservation and assess its implementation by the regional government. Using a normative legal research method grounded in the 1945 Constitution and relevant legislation, the study employs a statutory approach supplemented by empirical data collection. Findings indicate that Malinau Regency possesses the authority to enact regional regulations to safeguard local arts and culture from the erosion of traditional values. Such regulations are essential to ensure the sustainability of cultural heritage and must balance academic, ideological, sociological, and economic interests. Furthermore, regional regulations should empower local authorities and promote community participation in the protection, development, utilization, guidance, and supervision of regional culture.